The association between optimism, self-acceptance, gender role beliefs and mental well-being among non-heterosexual Malaysians - Tan, Zhi Ying; Lai, Weng Yen; Tee, Li Jia (2022)
Past studies about the well-being of non-heterosexuals in Malaysia are rare as most of the studies about the community were related to STIs, heterosexuals' attitudes towards them, and health care barriers. However, according to the minority stress model, non-heterosexuals often face unique stressors, leading to lower mental well-being. As optimism, self-acceptance, and gender role beliefs can be related to the minority stress model, this study aims to determine the relationship between said variables with the mental well-being of Malaysian non-heterosexuals. The study was conducted through a quantitative research method with a cross-sectional survey research design along with a sample of 160 non-heterosexual Malaysians adults recruited through online platforms. The data was collected by distributing a survey that included the Warwick-Edinburgh Mental Well-Being Scale, Revised Life Orientation Test, Self-Acceptance of Sexuality Inventory, and Liberal Feminist Attitude and Ideology Scale: Domains and Items Gender Roles. Results showed that the overall mental well-being of Malaysian non-heterosexuals is moderate. Also, there is significant positive correlation between optimism and mental well-being, and significant negative correlation between gender role beliefs and mental well-being. Theoretically, this study provided statistical proof of the association between the fore mentioned variables and strengthen the relevance of minority stress model in Malaysian non-heterosexual community. Practically, this study can provide resources when formulating non-heterosexual related psychological intervention, policies and sources for future research.